Bridging zero-dimensional loss units with one-dimensional carbon nanotubes for gradient-laminated polyarylene ether nitrile composites toward absorption-enhanced electromagnetic interference shielding - Jiabin Hu; Yunfeng Guo; Yu Zheng; Ting Zhang; Shaoqian Zhou; Yani Chen; Mei Liu; Qian Xiao; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Microdomain contraction and crystalline refinement in polyarylether nitrile alloys for high-temperature dielectric stability - Ting Zhang; Hongbo Shen; Youbin Wan; Yani Chen; Qian Xiao; Shaoqian Zhou; Yunfeng Guo; Jiabin Hu; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Fluctuations in groundwater inflow induced by periodic fracturing of overlying strata with mining - Shuning Dong; Zhenfang Zhou; Yang Dong; Qiang Ji; Jiankun Xue; Tiantian Wang; Yutong Wang; Le Han; Peiqiang Gao; Shenghu Luo; Yingying Yao (Bulletin of Engineering Geology and the Environment, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Janus structured magnetic MOFs-polyarylether nitrile/MXene composite films with gradient interfaces for electromagnetic interference shielding and thermal management - Yunfeng Guo; Jiabin Hu; Xin Sun; Ting Zhang; Shaoqian Zhou; Liang He; Hongbo Shen; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Solvent-induced biphasic phase separated hydrogels: Synergistic energy dissipation for softness, ultra-tough and shape recovery - Jiahong Kang; Bozhi Wu; Shuning Chen; Ji Zhou; Huihui Shi; Lei Wen; Yuheng Huang; Xiaoran Gong; Meng Nie; Litao Sun (Chemical Engineering Journal, 2026)

Matrix crystallinity and nanofiller compatibility optimization of polyarylether nitrile nanocomposite films for enhanced high-temperature energy storage - Ting Zhang; Yani Chen; Shaoqian Zhou; Jinqi Wu; Yunfeng Guo; Jiabin Hu; Qian Xiao; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2025)

Architectural design and building-level infections during the early stage of COVID-19: A study of 2597 public housing buildings in Hong Kong - Qingyao Qiao; Chongyang Ren; Shuning Chen; Yuebing Liang; Ka Yan Yvonne Lai; Yulun Zhou; Eric Schuldenfrei; Chinmoy Sarkar; Chris Webster (Building and Environment, 2025)

Development of a Colloidal Gold Immunochromatographic Strip for Specific Detection of Photobacterium damselae subsp. piscicida - Shuning Zhang; Jianbai Zhang; Yan Gao; Dandan Zhou; Binzhe Zhang; Xuepeng Li; Jian Zhang (Journal of Fish Diseases, 2025)
Photobacterium damselae subsp. piscicida (Pdp) is characterised by high infectivity and mortality and wide distribution, resulting in substantial economic losses to the global aquaculture industry. Therefore, it is critical to develop a simple, rapid and accurate diagnostic method for Pdp detection. Herein, two Pdp‐specific monoclonal antibodies (mAbs 1H7 and 6E6) were obtained, indirect enzyme‐linked immunosorbent assay and immunofluorescence analysis confirmed that the mAbs specifically recognised the outer membrane of Pdp but could not recognise the other Gram‐positive or Gram‐negative bacteria, indicating good specificity. A colloidal gold immunochromatographic strip (CGICS) was developed here for Pdp detection by optimising the colloidal gold labeling and antibody coating conditions using 1H7 as a colloidal gold‐labelled antibody and 6E6 as a coated antibody. The CGICS exhibited a detection limit of 1 × 10 5 CFU/mL for Pdp and a detection time of 10 min. Cross‐reaction analysis revealed that the CGICS could specifically detect different Pdp isolates without cross‐reaction with the other bacterial species or the subspecies P. damselae subsp . damselae . Stability analysis revealed that the CGICS were stored in closed plastic packaging at 25°C and 4°C for more than 8 months. The CGICS retained their detection limit after 6 months at 4°C, and 4 months at 25°C. Using tissues from the experimentally challenged Lateolabrax maculatus , the CGICS and polymerase chain reaction revealed a 100% coincidence rate. These findings indicated that the established CGICS exhibits high specificity and sensitivity. It is rapid and simple for Pdp detection, making it a potential on‐site tool for Pdp detection in fish aquaculture.

Establishment and application of a duplex fluorescent quantitative PCR assay for H9N2 subtype avian influenza virus and infectious bronchitis virus - Wanting Zhou; Qiuyan Mao; Shuning Zhou; Tingting Li; Jie Tian; Xiaoqi Li; Shuo Liu; Cheng Peng; Zhibin Hu; Jinping Li; Guangyu Hou; Houhui Song; et al. (Virus Genes, 2025)

High-efficiency PMS activation by difunctional Co-Fe PBA/g-C3N4 S-scheme heterojunction for oxytetracycline degradation: Performance evaluation and mechanism insight - Junjie Chen; Shuning Yu; Xialiang Jiang; Cheng Chen; Liguo Shen; Renjie Li; Yanchao Xu; Mingzhu Zhou; Bisheng Li; Honjun Lin (Science of The Total Environment, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Insights into Mn loaded carbon-silica-membrane based catalytic ozonation process for efficient wastewater treatment: Performance and mechanism - Shuning Chen; Tengfei Ren; Zuoyong Zhou; Kechao Lu; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

Machine learning approaches to equilibrium burnup analysis for Molten Salt Reactor - Shuning Chen; Jun Zhou; Xiangzhou Cai; Chunyan Zou; Jingen Chen (Annals of Nuclear Energy, 2023)

Mn-doped carbon-Al2SiO5 fibers enable catalytic ozonation for wastewater treatment: Interface modulation and mass transfer enhancement - Tengfei Ren; Changpei Ouyang; Zuoyong Zhou; Shuning Chen; Mengxi Yin; Xia Huang; Xiaoyuan Zhang (Journal of Hazardous Materials, 2023)

Impacts of core parameters on the capability of Cf-252 production in an MSR - Chunyan Zou; Chenggang Yu; Jun Zhou; Shuning Chen; Shaopeng Xia; Yang Zou; Xiangzhou Cai; Jianhui Wu; Jingen Chen (Annals of Nuclear Energy, 2023)

Efficient catalytic ozonation via Mn-loaded C-SiO2 Framework for advanced wastewater treatment: Reactive oxygen species evolution and catalytic mechanism - Shuning Chen; Tengfei Ren; Xiaoying Zhang; Zuoyong Zhou; Xia Huang; Xiaoyuan Zhang (Science of The Total Environment, 2023)

The coupling of persulfate activation and membrane separation for the effective pollutant degradation and membrane fouling alleviation - Mingzhu Zhou; Junjie Chen; Shuning Yu; Binghong Chen; Cheng Chen; Liguo Shen; Bisheng Li; Hongjun Lin (Chemical Engineering Journal, 2023)

Application of a pump and treat system to addressing potential vapor intrusion risk in a karst terrane: design parameter optimization and performance evaluation - Shuning Dong; Hao Wang; Wanfang Zhou (Sustainable Water Resources Management, 2022)

Dynamic Characteristics of Water Inflow from a Coal Mine’s Roof Aquifer - Zhenfang Zhou; Shuning Dong; Hao Wang; Dewu Jin; Xiaodong Wang; Yang Dong; Shi Chen; Debin Li; Xingling Dong; Hongbo Shang (Mine Water and the Environment, 2022)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Influences on the performance of cement-based grout used to reform the upper Middle Ordovician limestone in Hanxing mining area - Liu Zhaoxing; Dong Shuning; Wang Hao; Zhao Chunhu; Zhou Zhenfang (Arabian Journal of Geosciences, 2021)

Introduction to Special Issue on Mine Water Inrushes: Risk Assessment, Mitigation, and Prevention - Shuning Dong; Wanfang Zhou; Hao Wang (Mine Water and the Environment, 2021)

Discussion on Some Topical Issues of Water Prevention and Control in Coal Mines - Shuning Dong; Wenzhong Zhang; Wanfang Zhou; Rui Chai; Hao Wang; Chunhu Zhao; Xingling Dong; Qiangmin Wang (Mine Water and the Environment, 2021)

Characteristics of Water Hazards in China’s Coal Mines: A Review - Shuning Dong; Hao Wang; Xiaoming Guo; Zhenfang Zhou (Mine Water and the Environment, 2021)

Sinkholes and their impacts on karst hydrogeology in a peatland complex of Northern Ontario, Canada - Shuning Dong; Hao Wang; Wanfang Zhou (Carbonates and Evaporites, 2020)

Data Analysis and Key Parameters of Typical Water Hazard Control Engineering in Coal Mines of China - Lin Mou; Shuning Dong; Wanfang Zhou; Wei Wang; Ang Li; Zhiyuan Shi (Mine Water and the Environment, 2020)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

The scale dependence of dispersivity in multi-facies heterogeneous formations - Shuning Dong; Zhenxue Dai; Jingsheng Li; Wanfang Zhou (Carbonates and Evaporites, 2018)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)